Analysis of Working Capital Turnover on Profitability: A Case from PT Telekomunikasi Indonesia, Tbk - Annisa Paramaswary Aslam (Fundamental and Applied Management Journal, 2023)
This study aims to analysis about the turnover of working capital on profitability at PT. Telekomunikasi Indonesia Tbk. In addition, this study purpose to know about the impact of The Covid-19 for the telecommunications sector. The pandemic has changed the needs and lifestyles of people who rely heavily on internet access and the government's hard work to uniformly distribute digital infrastructure across Indonesia. The sample set is the balance sheet and income statement at PT Telekomunikasi Indonesia Tbk for the 2015-2021. The data used in this research is secondary data from the published financial reports of PT. Telekomunikasi Indonesia Tbk through the Indonesia Stock Exchange (IDX) website. The results showed that high working capital turnover was not followed by a high level of profitability, and working capital turnover was low it resulted in a high level of profitability.